Mentality in Solomon Northup’s Twelve Years a Slave: Literature, Novel, Mentality, Twelve Years a Slave - Pundoko, Gwine; Mamentu, Agustine C.; Rombepajung, Paula A. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2025)
This study was carried out to reveal the mentality in Solomon Northup’s Twelve Years A Slave novel. This study was delimited on how to find the mentality Twelve Years A Slave. In analyzing this n, the writer focused only on the problems identified above. The main character Solomon was concentrated to analyze his mentality. This research applied qualitative research design because the data are in the form of quotation or description. In carrying out this research, the data were got from the novel entitled Solomon Northup’s Twelve Years A Slave as primary source and also supported by other relevant references such as books, documents and other sources about mentality are considered as secondary source. The study’s findings highlight Solomon Northup’s profound mental transformation during his enslavement ordeal in "Twelve Years a Slave." Initially content with freedom and family, his abduction into slavery triggers shock and fear. Adapting to survive brutality, Solomon’s intelligence and resilience shine through. His unwavering determination to regain freedom and reunite with family underscores the power of hope. Despite post-freedom psychological scars, Solomon’s journey illuminates shock, survival, resilience, despair, determination, and trauma’s interplay, showcasing human spirit strength against adversity. "Twelve Years a Slave" imparts life lessons on resilience, dignity, hope, empathy, trauma’s impact, and enduring challenges’ endurance. Solomon’s dignity amid dehumanization stresses self-worth importance. His hope and determination illustrate belief’s transformative force and emphasize empathy and compassion’s role against injustice. Solomon’s perseverance symbolizes triumph over adversity, advocating for human rights and equality. Future research could delve into similar themes across literature, employing varied approaches for deeper understanding.